Treatment preferences of originator versus biosimilar drugs in Crohn's disease; discrete choice experiment among gastroenterologists - Baji, Petra; Gulácsi, László; Lovász, Barbara D; Golovics, Petra A; Brodszky, Valentin; Péntek, Márta; Rencz, Fanni; Lakatos, Péter L (Scandinavian journal of gastroenterology, 2016)
OBJECTIVE: To explore preferences of gastroenterologists for biosimilar drugs in Crohn's disease. MATERIAL AND METHODS: Discrete choice experiment was carried out involving 51 Hungarian gastroenterologists in May 2014. The following attributes were used to describe hypothetical choice sets: 1) type of the treatment (biosimilar/originator), 2) severity of disease, 3) availability of continuous medicine supply, 4) frequency of the efficacy check-ups. Multinomial logit model was used to differentiate between three attitude types: 1) always opting for the originator, 2) willing to consider biosimilar for biological-naïve patients only, 3) willing to consider biosimilar treatment for both types of patients. Conditional logit model was used to estimate the probabilities of choosing a given profile. RESULTS: Men, senior consultants, working in inflammatory bowel disease center and treating more patients were more likely willing to consider biosimilar for biological-naïve patients only. Treatment type (originator/biosimilar) was the most important determinant of choice for patients already treated with biologicals, and the availability of continuous medicine supply in case of biological-naïve patients. The probabilities of choosing the biosimilar with all the benefits offered over the originator under current reimbursement conditions are 89% versus 11% for new patients, and 44% versus 56% for patients already treated with biological. CONCLUSIONS: For gastroenterologist, the continuous medical supply would be one of the major benefits of biosimilars. However, benefits offered in the scenarios do not compensate for the change from the originator to the biosimilar treatment of patients already treated with biologicals.
Keywords: Surveys and Questionnaires; Infliximab; Humans; lidé středního věku; discrete choice experiment; biosimilární léčivé přípravky; infliximab; výběrové chování; Aged; Antibodies, Monoclonal; dospělí; Female; zdraví - znalosti, postoje, praxe; Crohn Disease; senioři; lidé; Biologicals; Hungary; průzkumy a dotazníky; Maďarsko; Choice Behavior; Adult; ženské pohlaví; biosimilars; Male; Middle Aged; lékaři; Crohnova nemoc; Practice Patterns, Physicians'; monoklonální protilátky; lékařská praxe - způsoby provádění; Health Knowledge, Attitudes, Practice; mužské pohlaví; Physicians; Biosimilar Pharmaceuticals; Crohn’s disease; preference